DNA sequence differences of ampD mutants of Citrobacter freundii. - Stapleton, P (1995)
Three groups of mutants with increased levels of beta-lactamase synthesis were selected from Citrobacter freundii 382010 by beta-lactam antibiotics at concentrations just above the MIC. Uninduced cultures of the hyperinducible group had 3- to 5-fold more beta-lactamase activity than the parent strain, with one mutant (termed type b) expressing 19 times the activity of the parent strain; the partially derepressed group had a relative 55-fold increase, while fully derepressed strains exhibited a 460-fold increase. Upon induction by growth in the presence of cefoxitin (32 micrograms/ml) for 2 h, the hyperinducible and derepressed groups had similar relative beta-lactamase activities of 650 and 725, respectively. Induction of beta-lactamase activity from partially derepressed mutants resulted in a relative activity of only 240. The ampD gene including its promoter region was amplified from the parent strain and the mutant strains by PCR. The sequence of ampD from the parent strain showed only three nucleotide changes from a previously published sequence, none of which resulted in a change to the deduced amino acid sequence. Hyperinducible mutant strains of type a had an amino acid change of either a tryptophan in codon 95 to an arginine (Trp-95-->Arg) (three mutants) or Ala-158-->Asp (one mutant). The hyperinducible type b strain had the change Tyr-102-->Asp. The derepressed strains had the following changes: Val-33-->Gly (one mutant), Asp-164-->Glu (one mutant), and Trp-95-->termination codon (two mutants). We infer that the amino acid changes in the hyperinducible mutants result in altered AmpD activity, whereas, in contrast, they lead to an inactive protein in derepressed mutants. No nucleotide differences were found in the ampD gene from partially derepressed strains.